Microfluidic channel flow cell for simultaneous cryoelectrochemical electron spin resonance. - Wain, A; Compton, R; Le Roux, R; Matthews, S; Fisher, A (2007)
A novel microfluidic electrochemical channel flow cell has been constructed for in situ operation in a cylindrical TE011 resonant ESR cavity under variable temperature conditions. The cell has a U-tube configuration, consisting of an inlet and outlet channel which run parallel and contain evaporated gold film working, pseudo-reference, and counter electrodes. This geometry was employed to permit use in conjunction with variable temperature apparatus which does not allow a flow-through approach. The cell is characterized qualitatively and quantitatively using the one-electron reduction of p-bromonitrobenzene in acetonitrile at room temperature as a model system, and the ESR signal-flow rate response is validated by use of three-dimensional digital simulation of the concentration profile for a stable electrogenerated radical species under hydrodynamic conditions. The cell is then used to obtain ESR spectra for a number of radical species in acetonitrile at 233 K, including the radical anions of m- and p-iodonitrobenzene, o-bromonitrobenzene, and m-nitrobenzyl chloride, the latter three being unstable at room temperature. Spectra are also presented for the radical anion of 2-chloranthraquinone and the crystal violet radical, which display improved resolution at low temperatures.